Singing Like Germans : Black Musicians in the Land of Bach, Beethoven, and Brahms - Thurman, Kira (Book collections on Project MUSE., 2021)
"This book examines the history of Black musicians in Germany and Austria in the nineteenth and twentieth centuries"--